Bibliometric Analysis of Research Regarding Citarum River in Indonesia and Its Implication for Government Policy - Endyana, Cipta; Hafiar, Hanny; Prastowo , Ari Agung; Fudholi, Ahmad; Amin, Kholidil (Journal of Local Government Issues, 2023)
Research mapping related to river revitalization has been carried out on areas experiencing severe pollution to provide a roadmap for knowledge and answers to a number of environmental issues surrounding rivers. Therefore, this study aims to map a number of research publications regarding the Citarum River, which is an important area for people in West Java. This river is currently the most polluted in Indonesia, which led to the implementation of the revitalization program initiated by the government known as "Citarum Harum". The bibliometric method was used in this research to determine annual trends, keywords, field grouping, and location. The results showed a fluctuating increase in the number of research publications on the Citarum River. Furthermore, the mapping results showed that topics, study groups, and locations related to this river were unevenly distributed. These findings indicated the need for coordination from the “Citarum Harum” program coordinator or government to develop a research roadmap and direct the researcher to examine topics and raise issues related to locations that are yet to be studied.